PERBANDINGAN FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA DI INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - Putri, Adinda; Azzahra, Alya; Andiany, Denita Dwi; Abdurohman, Dicki; Sinaga, Prido Putra; Yuhan, Risni Julaeni (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
Since Covid-19 arrived in Indonesia, all policies have been carried out to stop the spread of this virus, one of which is the PSBB. The impact of the PSBB is felt by the drastic increase in the number of unemployed in Indonesia. Using Multiple Classification Analysis (MCA), this research was conducted in order to see the condition of the Open Unemployment Rate (TPT) in each province in Indonesia between before and during the pandemic, and to find out the factors that influenced it. The results show that both before and after the pandemic, provinces with an HDI below the national figure led to higher TPT. The growth rate of GDRP and UMP has a different effect between before and during the pandemic. Other results also show that before the pandemic, UMP had the greatest influence on TPT. But after the pandemic, the one that had the biggest impact was HDI.